THE ROLE OF PHRASEOLOGISMS IN LITERATURE AND POETRY TODAY - Jumayeva Sadbarg Mirolimovna (Western European Studies, 2024)
In this article, complete information about phraseologisms, their importance and application, as well as the main features and types of phraseologisms, ways of effective use in communication are analyzed. Not only in communication, but also in literature, the wide use of phraseologisms and their importance in poetry are discussed.
Keywords: communication; speech culture; pronunciation; expression